Vicarious Kinks: S/M in the Socio-Legal Imaginary - UMMNI KHAN (University of Toronto Press, 2014)
I begin this book with an origin story to hint at my stakes in the topic at hand. Hoping that my confessional will have a seductive effect on the reader, I wrote a dramatization of a micro-battle in which I engaged (both internally and externally) during the so-called feminist sex wars. Both personal and biographical, the impact of the narrative relies on memory to project the past onto a screen of truth. Yet such a documentation of past experiences, as Hayden White has pointed out, â€œarises out of a desire to have real events display the coherence, integrity, fullness, and closure of an image of life that is and can only be imaginaryâ€ (White 1987, 24). The chronology of my screenplay offers a classic narrative, complete with the initial set-up (establishing my affiliation with the feminist community), catalyst (meeting Daphne, who challenges my feminist understandings of sexuality), rising action (arguments with Daphne and then Dragyn about the meaning of s/m), climax (attending a fetish night), and denouement (doing legal research on sexual rights). As White observes, â€œWhere in any account of reality, narrativity is present, we can be sure that morality or a moralizing impulse is present tooâ€ (24). The story romanticizes sexual alterity, with an underlying critique of the ideological constraints around sexual citizenship.1 In short, accounts of s/m â€“ including my own â€“ always involve normative storytelling. This book investigates some of the stories society spins about the truth of s/m. Practitioners tell us that s/m rests on appropriating social hierarchies, restaging power imbalances, and/or re-signifying pain within a consensual context. As such, s/m desires are based on the drive to retell a particular story, to replay a particular scene, but in a way that seeks to transmute the social scripts from which it borrows (McClintock 1993, 89). But my focus here is not on s/m itself. Rather, I examine how three major cultural discourses and frameworks about s/m â€“ science, feminism, and film â€“ interact with one another, and with lawâ€™s construction of s/m as an object of knowledge.